Using Physical Signaling to Support Collaborative Mobile Search - Teevan, Jaime; Morris, Meredith Ringel; Azenkot, Shiri (Extended Abstracts of CSCW 2014, 2014)
Often when people search the web from their phones, they do so collaboratively. We present a mobile application that supports in-person collaborative search by allowing users to physically signal a willingness to share. While the core application provides standard mobile search functionality, users rotate their devices to landscape orientation to indicate (to the device and others) they are entering a collaborative mode. We study two uses of collaborative mode, one where users rate results to create a group list, and another where screens and actions are shared across devices.